Utilization of the Time Driven Activity Based Costing Method in Determining the Cost of Room Rent at Hotel Tampiarto Probolinggo - Tatik Amani; Khusnik Hudzafidah; Hanifah Indah Wulandari (Universitas Pendidikan Ganesha, 2021)
The determination of the cost of renting a room at the Hotel Tampiarto Probolinggo is currently still using traditional methods that lack accuracy. Time driven activity-based costing method can solve these problems by presenting an accurate cost of room rental. This study aims to calculate and present hotel room rental prices with the time driven activity-based costing method and to find out the difference between the traditional method and the time driven activity-based costing method. The method in this research is descriptive qualitative with a case study approach. The subject of this study is the rental price of all rooms at Hotel Tampiarto Probolinggo. The results of calculations and analysis in this study indicate that the calculation of the cost of renting a hotel room with the Time Driven Activity Based Costing method can be applied by Hotel Tampiarto because the results show that the allocation of costs for each activity based on the time required produces a more accurate and efficient cost of renting a room with the average efficiency rate of each room is 8% to 30% of the current price of traditional methods.With the cost of goods using the time driven activity based costing method, management can make business strategies to increase room rental income by making new strategies, especially for the type of room with the lowest sales level with cheaper room rental costs.